Developing Prosocial Skills in 4–5-Year-Olds Through Collaborative Learning Models: A Qualitative Study - Wulandari, Iswara Indah; Suhma, Fihris Maulidiah (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
This study examines the implementation of group learning models to foster prosocial behavior in children aged 4–5 at a Kindergarten. Using a qualitative approach with observations, interviews, and documentation, the research highlights the role of structured planning, engaging implementation, and comprehensive evaluation in enhancing cooperation, responsibility, and creativity. Findings reveal significant improvements in prosocial behavior, with 16 out of 17 children meeting developmental expectations. Despite challenges such as resource constraints and subjective assessments, the study emphasizes the potential of group learning to promote social-emotional development in early childhood education. Recommendations include enhanced teacher training and innovative evaluation methods to optimize outcomes.